Acute injuries in Olympic Fencing: Athens 2004 and Beijing 2008 - Rodriguez Rey, E. R. (Archivos de medicina del deporte, 2008)
Introduction: Data was collected concerning injuries suffered by athletes competing in the Athens 2004 and Beijing 2008 Olympic Fencing events. The limited number of participants and competition pattern in Olympic Fencing enhances some of the known sport-specifi c injuries, while others vary. Some changes where observed in the injury statistics of the two subsequent Olympic Games. Injury-prevention measures are thus suggested. Material and Methods: There are signifi cant differences in the competition organization in World and Continental Championships and the Olympic Games. The first two are based on poule (group) elimination rounds of individual competition, with 5-6 bouts per fencer, to then go on to 128, 64 and 32 Direct Elimination bouts. In the Olympic Games, competition begins with Direct Elimination of 32, so the fencing is less and more intense. International Fencing Federation (FIE) forms where used to collect information regarding injury number, date, gender, diagnosis and hospital transfer, when needed, during the Fencing events of the Athens 2004 and Beijing 2004 Olympic Games. The injured regions where divided into Head, Spine (SP), Upper Extremity (UE) and Lower Extremity (LE). The limited number of participants and direct elimination bouts in Olympic Fencing lessens the statistic signifi cance of the data collected, but we fi nd it adds information concerning injury type. Results: In the Athens 2004 group, it was found that the total recorded injuries were 34, in the Beijing 2008 group they numbered 25, where it must be noted that in 2004 12 Olympic titles were at stake, a number reduced by the International Olympic Committee to 10 in 2008.The competing total of athletes in Beijing was 344 in the individual and team events, with a similar number per event in Athens, taking into account that 2 additional titles were at stake. In the Athens 2004 group, the Head accounted 1 injury (ocular foreign body); the SP suffered 5 injuries, of which 4 were lower back pain; the UL suffered 11 injuries, of which 3 were elbow sprains and 3 others hand wounds; the LE suffered 17 injuries, of which 4 were knee sprains and 5 ankle sprains. In the Beijing 2008 group, no injuries the Head nor SP were recorded; the UE suffered 25 injuries, of which 4 were contusions to the hand and 5 were cutting wounds to the hand; one shoulder dislocation on a previously injured athlete was recorded. The LE suffered 12 injuries, of which 6 were ankle sprains. Conclusions: The known patterns of injury in high-level fencing competition vary in the Olympic Games because of the much shorter and intense competition. Lower back pain has diminished sharply, whereas the common ankle sprain still is the most frequent injury in Fencing. A sharp rise has been observed in the percentage of wounds to the unprotected hand. It would be advisable to suggest protective measures to the ankle and hand, such as ankle strappings or supporting rods and gloving the unprotected hand.